Association between exposure to drinking water disinfection byproducts and adverse pregnancy outcomes in South Africa - Funanani Mashau (IWA Publishing, 2021)
Currently, there is contradictory evidence for the risk of adverse pregnancy outcomes associated with maternal exposure to disinfection byproducts (DBPs). We examine the association between maternal exposure to trihalomethanes (THMs) in drinking water and adverse pregnancy outcomes, including premature birth, low birth weight (LBW) and small for gestational age (SGA). In total, 1,167 women older than 18 years were enrolled at public antenatal venues in two geographical districts. For each district, we measured the levels of residential drinking water DBPs (measured in THMs) through regulatory data and routine water sampling. We estimated the individual uptake of water of each woman by combining individual water use and uptake factors. Increased daily internal dose of total THMs during the third trimester of pregnancy significantly increased the risk of delivering premature infants (AOR 3.13, 95% CI 1.36–7.17). The risk of premature birth was also positiviely associated with exposure to total THMs during the whole pregnancy (AOR 2.89, 95% CI 1.25–6.68). The risk of delivering an SGA and LBW infant was not associated with maternal exposure to THMs. Our findings suggest that exposure to THMs is associated with certain negative pregnancy outcomes. The levels of THMs in water should be routinely monitored.